Antagonism of microRNA function in zebrafish embryos by using locked nucleic acid enzymes (LNAzymes) - Suryawanshi, Hemant; Lalwani, Mukesh Kumar; Ramasamy, Soundhar; Rana, Rajiv; Scaria, Vinod; Sivasubbu, Sridhar; Maiti, Souvik (Chembiochem, 2012)
MicroRNAs (miRNAs) have crucial functions in many cellular processes, such as differentiation, proliferation and apoptosis; aberrant expression of miRNAs has been linked to human diseases, including cancer. Tools that allow specific and efficient knockdown of miRNAs would be of immense importance for exploring miRNA function. Zebrafish serves as an excellent vertebrate model system to understand the functions of miRNAs involved in a variety of biological processes. We designed and employed a strategy based on locked nucleic acid enzymes (LNAzymes) for in vivo knockdown of miRNA in zebrafish embryos. We demonstrate that LNAzyme can efficiently knockdown miRNAs with minimal toxicity to the zebrafish embryos.
Keywords: enzymes; locked nucleic acids; microRNA; morpholino; zebrafish

Anti-cancer therapeutic potential of quinazoline based small molecules via global upregulation of miRNAs - Nahar, Smita; Bose, Debojit; Panja, Sumit Kumar; Saha, Satyen; Maiti, Souvik (Chemical Communications, 2014)
Three quinazoline based small molecules showed global upregulation of miRNA expression with a selective enrichment of tumor suppressor miRNAs. The target genes of the upregulated miRNAs were predicted to be enriched for apoptotic pathways. Apoptotic induction following treatment with quinazoline compounds was confirmed by in cellulo studies. Thus, these small molecules having the core structural moiety (2,4-diphenyl-quinazoline) can be used as scaffolds to design activators of miRNA expression paving the way for novel anti-cancer drugs.

Alternative splicing modulation mediated by G-quadruplex structures in MALAT1 lncRNA - Ghosh, Arpita; Pandey, Satya Prakash; Ansari, Asgar Hussain; Sundar, Jennifer Seematti; Singh, Praveen; Khan, Yasmeen; Ekka, Mary Krishna; Chakraborty, Debojyoti; Maiti, Souvik (Nucleic Acids Research, 2022)
MALAT1, an abundant lncRNA specifically localized to nuclear speckles, regulates alternative-splicing (AS). The molecular basis of its role in AS remains poorly understood. Here, we report three conserved, thermodynamically stable, parallel RNAG-quadruplexes (rG4s) present in the 3' region of MALAT1 which regulates this function. Using rG4 domain-specific RNA-pull-down followed by mass-spectrometry, RNA-immuno-precipitation, and imaging, we demonstrate the rG4 dependent localization of Nucleolin (NCL) and Nucleophosmin (NPM) to nuclear speckles. Specific G-to-A mutations that abolish rG4 structures, result in the localization loss of both the proteins from speckles. Functionally, disruption of rG4 in MALAT1 phenocopies NCL knockdown resulting in altered pre-mRNA splicing of endogenous genes. These results reveal a central role of rG4s within the 3' region of MALAT1 orchestrating AS.